Career adaptability and career construction as mediating variables between hardiness and vocational identity - Merino-Tejedor, Enrique; Serrano-Fernández, María-José; Boada-Cuerva, Maria; Sora, Beatriz (International journal for research in vocational education and training, 2025)
Background: The Career Construction Theory (CCT) focuses on the active role people can play when they create and design their singular paths for career success. Unlike other career guidance theories that focus their attention on identifying vocational interests or on the fit between the person and the work settings, CCT raises the possibility that people can go beyond the determinants of their life. This study tested the adaptation model proposed by Career Construction Theory. Consolidation of vocational identity is particularly important at the university stage, in which people decide their first steps about their professional future. Method: Participants were 1023 students from Spain and Brazil. The Spanish subsample was composed of 602 participants, 34% were men (N = 207), and 66% were women (N = 395). The average age was 21.69. The Brazilian subsample was composed by 421 participants, 39% were men (N = 165), and 61% were women (N = 256), with an average age of 24.84. The four dimensions in the model were each operationally defined by a single indicator. The Hardiness Scale represented adaptive readiness.